2019
DOI: 10.1007/s10803-019-04016-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Who Am I?’: An Exploratory Study of the Relationships Between Identity, Acculturation and Mental Health in Autistic Adolescents

Abstract: Autistic adolescents are at increased risk of mental health difficulties. One potential factor contributing to this is identity development, although this hypothesis has been little explored. These adolescents also have to consider how autism forms their identity, a process called acculturation. This exploratory study examined the relationships between identity, acculturation and mental health in autistic adolescents. Twenty-four participants completed measures investigating identity, acculturation and mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 91 publications
(107 reference statements)
4
15
1
Order By: Relevance
“…This supports findings from a recent study evaluating an autistic-led support programme for autistic adults, which found that in exploring their experiences as autistic individuals, participants developed a sense of unity in their diverse experiences of autism (Crane et al 2020 ). Cresswell and Cage ( 2019 ) found that autistic participants who were more aligned with non-autistic culture generated more positive self-statements, which conflicts with our finding that autistic people who generated more positive autism attributes also had more positive collective self-esteem and stronger autism social identity. These discrepancies are likely due to the different constructs measured, with Cresswell and Cage’s study focussing on general self-statements and not autism related traits.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This supports findings from a recent study evaluating an autistic-led support programme for autistic adults, which found that in exploring their experiences as autistic individuals, participants developed a sense of unity in their diverse experiences of autism (Crane et al 2020 ). Cresswell and Cage ( 2019 ) found that autistic participants who were more aligned with non-autistic culture generated more positive self-statements, which conflicts with our finding that autistic people who generated more positive autism attributes also had more positive collective self-esteem and stronger autism social identity. These discrepancies are likely due to the different constructs measured, with Cresswell and Cage’s study focussing on general self-statements and not autism related traits.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, the extent to which an autistic person accepts their autism identity, and feels society accepts their autism, has been found to be negatively associated with depression scores in autistic adults (Cage et al 2018 ). However, a study with 24 autistic adolescents found that autistic individuals who aligned themselves to non-autistic culture generated more positive self-statements than those who did not align themselves with either autistic or non-autistic culture (Cresswell and Cage 2019 ). Mixed findings about how positively autism identity is perceived are prevalent in qualitative research in the field, with some participants emphasising strengths, others emphasizing challenges and many with a balanced perspective (Macleod et al 2013 ; Mogensen and Mason 2015 ; Cage et al 2016 ).…”
mentioning
confidence: 95%
“…Similarly, autistic adults who camouflage more report feeling a reduced sense of belonging, and higher levels of suicidality [21]. Individuals who camouflage more may have lower self-esteem and fewer close relationships, both of which are associated with poor mental health outcomes [56,57]. Negative outcomes of camouflaging have been previously reported by autistic adults of multiple genders [34,53].…”
Section: Discussionmentioning
confidence: 85%
“…56 Such information will also have sociological effects too. The increasingly vocal voices from the autism spectrum discussing autism as an identity 57 over and above just a clinical diagnosis will no doubt be affected by discussions about autism not being innate and/or life-long for everyone.…”
Section: Discussionmentioning
confidence: 99%